2011
DOI: 10.1159/000329979
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis Suppressor KAI1/CD82 Attenuates the Matrix Adhesion of Human Prostate Cancer Cells by Suppressing Fibronectin Expression and β <sub>1</sub> Integrin Activation

Abstract: KAI1/CD82, a tetraspanin membrane protein functions as a metastasis suppressor in many types of human cancers and has been shown to regulate cell adhesion properties. In the present study, we investigated the underlying mechanism of KAI1/CD82-mediated changes in cell adhesion to the extracellular matrix using human prostate cancer cells. We found that high KAI1/CD82 expression attenuated short-term cell adhesion to uncoated- or fibronectin-coated plates. Moreover, high KAI1/CD82 expression generated an extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…Increasing attention has been paid to the interaction between different factors involved in metastatic processes in hormone-sensitive tumors [22][23][24]. To our knowledge, this is the first study which has analyzed the association between steroid receptors, KAI1 protein, MMP-2, and MMP-9 -as well as between KAI1, MMP-2, and MMP-9 Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing attention has been paid to the interaction between different factors involved in metastatic processes in hormone-sensitive tumors [22][23][24]. To our knowledge, this is the first study which has analyzed the association between steroid receptors, KAI1 protein, MMP-2, and MMP-9 -as well as between KAI1, MMP-2, and MMP-9 Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of KAI1 expression was associated with advanced stages of many malignancies including prostate, colon, lung, pancreatic, breast, ovarian and other cancers (6,7). KAI1 belongs to transmembrane 4 superfamily (TM4SF), encoding a 267 amino acid glycosylated membrane protein with four highly conserved transmembrane domain.…”
Section: Introductionmentioning
confidence: 99%
“…45 Subsequent studies have suggested that the antimetastatic effects of CD82 are mediated by inhibition of integrin-dependent activation of c-Met and Src kinases as well as suppression of fibronectin expression and b1 integrin activation. [46][47][48] Other studies have shown that CD82 inhibits Tetraspanins are composed of 4 transmembrane domains (pink), a small (EC1) and a large extracellular domain (EC2), a very small intracellular domain, and short cytoplasmic N-and C-terminal tails. The EC2 contains a variable region presenting a conserved Cys-Cys-Gly (CCG) motif and 2-6 additional cysteine residues, which form intramolecular disulfide bonds (red dotted lines).…”
mentioning
confidence: 99%